Bridging Vocational Needs with Chemistry Content: Designing an Outline of Chemistry Teaching Materials for Textile Dyeing Context - Muhammad Syahrur Royhan; Sjaeful Anwar; Ijang Rohman (Postgraduate, University of Mataram, 2025)
The merging of adaptive chemistry subjects (C.1) into the IPAS project subject in the Independent Curriculum causes the chemistry content to be non-specific and not adapted to all vocational elements. This has the potential to hinder students' understanding of relevant chemistry concepts in their vocational context. This study aims to design an outline of chemistry teaching materials that are relevant to the needs of dyeing subjects in Textile Finishing Engineering VHS. The method used is Qualitative Content Analysis (QCA) with four stages to obtain and evaluate chemistry content related to the dyeing context. The results show that there are 19 chemistry contents that have been systematically arranged and validated based on the sequence, details, and their relationship to the dyeing context. For example, the content of electrolyte solution, acid base, ion equilibrium in solution, and reaction rate plays an important role in regulating the affinity of dyes to fibers and the speed of the dyeing process. This outline is useful for teachers or education practitioners as a clear guide to integrating chemistry content and vocational contexts into learning or teaching materials. For students, it can help them understand chemistry concepts that are more contextual and applicable to their vocational fields.